Instytucje gwarancji kredytowych dla małych i średnich przedsiębiorstw - rys historyczny - Adamek, Jacek (Credit guarantee institutions for small and medium enterprises - historical outline, 2005)
160 years have just passed since the establishment of the first guarantee institution, which directed its securitization products towards small and medium size enterprises. Since then thousands of credit guarantee corporations have been established, presenting diversified organizational and operational formula. The objective of the hereby study is an attempt to provide characteristics of historical evolution typical for credit guarantee institutions functioning at all continents in the world.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 73-80